Titer Antibody of Newcastle Disease in Layer Chicken in Narmada District, West Lombok - Agustin, Alfiana Laili Dwi; Ningtyas, Novarina Sulsia Ista'In (Universitas Airlangga, 2021)
Newcatle disease (ND) is a disease in poultry that can cause considerable losses for farmers. Common symptoms seen at the beginning of infection are decreased appetite for chickens, lethargy, conjunctivitis, and decreased egg production. There is no effective treatment for ND disease. One of the efforts to prevent ND is to do vaccination and good biosecurity. This study aimed to determine ND antibody titer in layer chicken in Narmada district, West Lombok. The serum sample used was 87 divided according to the length of post vaccination 4 weeks, 8 weeks and 12 weeks post vaccination. The method used to determine the antibody profile was the Haemaglutination inhibition test. A total of 87 serum chickens were sampled, and the antibody titer was still protective 26-211. Measuring antibody titer can help farmer to make health programs even better, so that livestock more resistant to virus infection.